Rewriting the book of the city: on old signs, new technologies, and reinventing Adelaide. Issue 1 (2nd January 2017) - Schutt, Stefan
ABSTRACT: Can a sense of ownership over constantly changing urban places be generated through pedestrian exploration and everyday digital media practice? This paper begins with the author's visit to the city of Adelaide, where a chance encounter – an intriguing sign painted on the wall of a city building – led to a hunt through the city for ghost signs, the remnants of old hand-painted advertisements. This spontaneous activity, combined with the online exploration and image sharing that followed, generated a renewed feeling of connection to, and ownership over, an erstwhile familiar locale. The experience is analysed through the work of theorists investigating change and belonging in modern cities including Guy Debord, Doreen Massey, Michel de Certeau, Andreas Huyssen, and Mark Crinson, as well as the contemporary growth in both politically inspired urban exploring ("Urbex" or "place hacking") and the digital documentation and sharing of ghost signs and other urban ephemera.